(untitled) - Trịnh, Quốc Lập (Cần Thơ, 2002)
It is composed of two parts. Part I presents the research issues regarding early stages of language development of both first and second language learners, how some grammatical features such as negation, grammatical morphemes... Part II consists of some further reading on problems related to second language qcquisition.
Keywords: Second language acquisition